2012
DOI: 10.14234/elehe.v4i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Using culturally relevant case studies to enhance students’ learning: a reflective analysis of the benefits and challenges for social work students and academics

Abstract: Internationalising the curriculum', 'multi-cultural education', 'culturally sensitive' education, and 'culturally competent teaching' are terms often used to describe teaching and learning which provides opportunities for learning about multiple and diverse contexts in which specific aspects of knowledge can be applied. In social work education, there is a growing call for an international outlook in teaching and practice learning to enhance the experiences of learners and also to prepare graduates for working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Often, the literature focuses on the pedagogical implications of cultural difference for learning (see e.g. Bartoli et al, 2008;Bartoli, 2011, Tedam, 2012. For example, Bartoli (2011) examines data about African students' academic grades on a social work programme to draw conclusions about their perceptions of particular assessment methods, compared with how they performed-a potentially valuable focus given the lack of attention to this topic more broadly.…”
Section: Cultural Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Often, the literature focuses on the pedagogical implications of cultural difference for learning (see e.g. Bartoli et al, 2008;Bartoli, 2011, Tedam, 2012. For example, Bartoli (2011) examines data about African students' academic grades on a social work programme to draw conclusions about their perceptions of particular assessment methods, compared with how they performed-a potentially valuable focus given the lack of attention to this topic more broadly.…”
Section: Cultural Differencementioning
confidence: 99%
“…The fourth concept concerns how solutions to some of the (perceived or actual) difficulties facing BME students are arrived at. Tedam (2012) for example, invokes the idea of cultural difference to explain how African students struggle to understand aspects of the social work curriculum and the need for Afrocentric approaches to demystify and make accessible western academic literature and philosophy. The article reports on a case study describing individual teaching with one Zimbabwean student, where culturally relevant examples were used to aid understanding of Social Learning theory.…”
Section: Pedagogical Solutionsmentioning
confidence: 99%
“…With specific reference to BME students of social work, Goldingay (2012) proposes that in order to enhance their placement experiences HEIs spend time in pre-placement planning and support, particularly for international students, as her research evidenced the value of such a strategy. It has been argued elsewhere (Tedam, 2012a) that the use of culturally relevant case studies can support and develop the social work knowledge base for specific ethnic minority students. Hair and O'Donoghue (2009) have suggested that social work supervision has the potential to contribute to the 'marginalization of people according to cultural identities such as ethnicity, race, gender, or class' (p.71) and in order to address this, the MANDELA model (Tedam, 2012b) was developed to support anti-oppressive practice supervision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Participants in this study did not neglect the role of the student when highlighting strategies that might be helpful; instead they placed a significant burden of the strategy on themselves as social work students. Tedam (2012aTedam ( , 2012bTedam ( and 2013 attempted to contribute to remedying the shortage of culturally relevant teaching and learning materials for black African students of social work in the hope that practice educators specifically and social work educators more generally would find them useful.…”
Section: Implications For Social Work Educationmentioning
confidence: 99%
“…On a personal level, I have sought to develop ideas that might enhance the teaching and learning experiences of BME students enrolled on social work programmes. These ideas have been disseminated elsewhere (Tedam, 2012a(Tedam, , 2012b and were motivated by an observation made by a black social work student in a large urban university in the United States, who concluded that students appreciated 'literature about people of colour by people of colour' (Daniel, 2011, p.255). This, in addition to a call for black academics and researchers to contribute to knowledge creation, has not gone unheeded.…”
Section: Introductionmentioning
confidence: 99%